Profil Minat Belajar Siswa Kelas X MAN 4 Madina pada Mata Pelajaran Bimbingan Konseling Tahun Ajaran 2021-2022 - Cahyana, Wilda; Afrinaldi, Afrinaldi; M, Iswantir; Santosa, Budi (Institut Teknologi Pendidikan Indonesia, 2023)
The background of this research was found that student's interest in the guidance and counselingsubject was relatively low. Students also think that guidance and counseling subjects are subjects that do not require study hours because the material presented can be found in everyday life. This study aims to describe the Learning Interests of Class X MAN 4 Madina in Guidance and Counseling Subjects for the 2021/2022 Academic Year. This study used a qualitative descriptive type approach with 8 key informants from class X MAN 4 Madina and a supporting informant 1 counseling teacher who taught class X MAN 4 Madina in Simpanggambir Village, Linggabayu District. In collecting data, researchers used to interview and observation methods. The data analysis technique used is data reduction, data display, and data verification. To test the validity of the data, namely by comparing what people say about the research situation with what is said all the time. The results of the research from the data obtained indicate that the profile of interest in learning in participating in counseling activities for class X MAN 4 Mandailing Natal as a whole is still not good if it is categorized as Medium Category. In research conducted from the aspect of feelings, some students have feelings ofpleasure in participating in counseling guidance service activities, and some students feel normalbecause these students do not understand well how counseling will affect their daily lives. And from the aspect of student attention to learning is still very lacking. The learning materials provided are sometimes less attractive to students and lack student participation in playing an active role in the guidance and counseling activities carried out.